Pantoprazole Does not Affect Serum Trough Levels of Tacrolimus and Everolimus in Liver Transplant Recipients - Bremer, Sebastian C. B.; Reinhardt, Lars; Sobotta, Michael; Hasselluhn, Marie C.; Lorf, Thomas; Ellenrieder, Volker; Schwörer, Harald (Frontiers in Medicine, 2018)
Background: Liver transplant recipients are frequently treated with proton pump inhibitors. Drug interactions have been described especially with respect to omeprazole. Due to the lower binding capacity of pantoprazole to CYP2C19 this drug became preferred and became the most used proton pump inhibitor in Germany. The data on the influence of pantoprazole on immunosuppressive drugs in liver transplant recipients a very scarce. Methods: The authors performed a single center analysis in liver transplant recipients on the effect of pantoprazole on the serum trough levels of different immunosuppressants. The trough levels were compared over a period of one year before and after start or stop of a continuous oral co-administration of 40mg pantoprazole once daily. Results: The serum trough levels of tacrolimus (n=30), everolimus (n=7) or sirolimus (n=3) remain constant during an observation period of at least one year before and after co-administration of pantoprazole. None of the included patients needed a change of dosage of the observed immunosuppressants during the observation period. Conclusions: The oral co-administration of pantoprazole is safe in immunosuppressed liver transplant recipients according to the serum trough levels of tacrolimus, everolimus and sirolimus. This analysis provides first data on the influence of pantoprazole on immunosuppressive drugs in liver transplant recipients.